Leadership Type for Accelerating Digital Transformation at the Sub-District Level - Mamuaja, Marlin Penina; Rawis, Joulanda A.M.; Tambingon, Henny N.; Kambey, Joseph (International Journal of Information Technology and Education, 2023)
Each leader types the other's leadership. Camat Tondano Selatan which has been relatively considered successful make researcher interested In knowing the type of leadership that belongs to Camat. Digital transformation has become a very important thing in increasing the quality of service in the public-level district. However, transformation needs effective leadership to reach optimal results. This article aims to analyze the type of most effective leadership in pushing digital transformation on the level district. The method used in this research is method study comparison. The comparison was done between two of the variables studied to see variable tendencies. Amount of whole office employee subdistrict South Tondano totaled 22 people plus 8 Lurah, a total of 30 people. because amount employees plus the village chief only 30 people then in the study This researcher use whole officials and village heads as sample research. Research results show that the average value of the answers questionnaire from respondent research is 4.1567 for type leadership transformational and 3.2767 for type leadership transactional. In other words employees in the District and Lurah are in the District area Tondano Selatan assessed that type the of the leadership of the Camat Tondano Selatan is more tend to Type Leadership transformational compared to with the type of leadership transactional. The result is a significant difference between the second type of average value leadership. it can be seen in the t value of 48.280 which is significant at an alpha value of 0.5. Research results also show that type of effective leadership in speeding up digital transformation at the level subdistrict is leadership transformational and leadership participatory. Leadership transformational can push innovation and creativity in the development of digital solutions, meanwhile, leadership participatory can increase the involvement of staff in the digital transformation process. Study This recommends that the head district and related staff with digital transformation in the sub-district must adopt type leadership transformational and participatory for speeding up digital transformation at the level district.